Sexing la mode gender, fashion and commercial culture in old regime France - Jones, Jennifer Michelle (Bloomsbury Fashion Central, 2021)
The connection between fashion, femininity, frivolity and Frenchness has become a clich . Yet, relegating fashion to the realm of frivolity and femininity is a distinctly modern belief that developed along with the urban culture of the Enlightenment. In eighteenth-century France, a commercial culture filled with shop girls, fashion magazines and window displays began to supplant a court-based fashion culture based on rank and distinction, stimulating debates over the proper relationship between women and commercial culture, public and private spheres, and morality and taste. Mary Wollstonecraft was one of those particularly critical of this 'vulgar' obsession with 'tawdry finery', declaring it to be 'merely the external mark of a depravity shared with slaves'. The story of how la mode was 'sexed' as feminine offers a compelling insight into the political, economic and cultural tensions that marked the birth of modern commercial culture. Jones examines men's and women's relation to fashion at this time, looking at both consumption and production to argue how clothing was becoming increasingly conceptualized as feminine/effeminate. A concise history of French fashion culture suitable for anyone interested in eighteenth-century culture, women and gender studies or fashion history